2013
DOI: 10.3389/fpsyg.2013.00532
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin and social pretreatment have similar effects on processing of negative emotional faces in healthy adult males

Abstract: Oxytocin has been shown to affect several aspects of human social cognition, including facial emotion processing. There is also evidence that social stimuli (such as eye-contact) can effectively modulate endogenous oxytocin levels. In the present study we directly tested whether intranasal oxytocin administration and pre-treatment with social stimuli had similar effects on face processing at the behavioral level. Subjects (N = 52 healthy adult males) were presented with a set of faces with expressions of diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 65 publications
(79 reference statements)
2
12
0
1
Order By: Relevance
“…Accordingly, heightened generosity ( van Baaren et al , 2003 ) and visual preference or affiliative behaviors towards an imitating person ( Field et al , 2001 ) may thus depend on increased OXT secretion in the imitated person. In fact, it has been reported that a social interaction pretreatment has a similar effect as the intranasal administration of OXT on the processing of negative emotional faces ( Kis et al , 2013 ). Against this background, therapeutic interventions fostering imitation or synchronization in general ( Koehne et al , 2016 ), may constitute an efficient non-pharmacological probe to increase OXT levels and improve social skills.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, heightened generosity ( van Baaren et al , 2003 ) and visual preference or affiliative behaviors towards an imitating person ( Field et al , 2001 ) may thus depend on increased OXT secretion in the imitated person. In fact, it has been reported that a social interaction pretreatment has a similar effect as the intranasal administration of OXT on the processing of negative emotional faces ( Kis et al , 2013 ). Against this background, therapeutic interventions fostering imitation or synchronization in general ( Koehne et al , 2016 ), may constitute an efficient non-pharmacological probe to increase OXT levels and improve social skills.…”
Section: Discussionmentioning
confidence: 99%
“…The rationale of Experiment 1 was to generate normative cues for altruistic responding toward refugees. For this purpose, [40][41][42][43][44][45] min before the start of the donation task. The placebo solution contained the identical ingredients except the peptide itself.…”
Section: Methodsmentioning
confidence: 99%
“…Depending on the experimental task, however, oxytocin also influences neural activity in other brain regions, including temporoparietal junction (TPJ) (Domes et al, 2007), ventral prefrontal cortex (PFC), fusiform (Petrovic et al, 2008), and insula (Striepens et al, 2012), suggesting that oxytocin's regional neural influence is context-specific. Such oxytocin-induced modulations of neural activity may underlie oxytocin's anxiolytic and prosocial effects in humans (Evans et al, 2010;Heinrichs et al, 2003;Kis et al, 2013;Kosfeld et al, 2005;Norman et al, 2011;Petrovic et al, 2008;Theodoridou et al, 2009). Human vasopressin studies are less abundant; however, several investigations support opposing roles of oxytocin and vasopressin, with the latter being associated with aggression and anxiogenic behaviors (Ebstein et al, 2009;Thompson et al, 2004).…”
Section: Introductionmentioning
confidence: 99%